The future of Holocaust memorialization : confronting racism, antisemitism, and homophobia through memory work - Pető, Andrea 1964-; Thorson, Helga (Bonex Press KFT, 2015)
Andrea Pető and Helga Thorson Introduction: The Future of Holocaust Memorialization -- Paul Shapiro Facing the Facts of the Holocaust: The Challenges and the Cost of Failure -- Karen Jungblut The Future of Holocaust Memorialization: Institutional Perspectives and Challenges -- Cecilie Felicia Stokholm Banke : Teaching the Holocaust as Part of Local History: The Case of Denmark -- Klas-Göran Karlsson Holocaust History and Historical Learning -- John C. Swanson Returning to History: Memory and Holocaust Education -- Helga Dorner, Edit Jeges, and Andrea Pető New Ways of Seeing: Digital Testimonies, Reflective Inquiry, and Video Pedagogy in a Graduate Seminar -- Elizabeth Anthony The Digital Transformation of the International Tracing Service Digital Collection -- Ildikó Barna Introducing a New Subject in a Challenging Environment among Students of Military Sciences, Public Administration, and Law Enforcement in Hungary: A Case Study -- Heike Radvan Facing Current Anti-Semitism, Racism, and Neo-Nazism: Talking about the Holocaust in Local Initiatives in East Germany -- Charlotte Schallié The Case of Feincost Adam: Confronting Antisemitism through Creative Memory Work -- Annamaria Orla-Bukowska Remembering Righteousness: Transnational Touchstones in the International Classroom -- Helga Thorson and Andrea van Noord Stories from the Past, Creative Representations of the Future: Inter-Cultural Exchange, the Possibility of Inter-Generational Communication, and the Future of Holocaust Studies -- Barbara Kintaert Shedding Light on the Past: Digging for Information and Grassroots Memorialization -- Borbála Klacsmann Memory Walk: History through Monuments -- Gabor Kalman Filming the Past for the Present